Encounters with the unfamiliar: international planning education. Issue 1 (2nd January 2018) - Ratnayake, Rangajeewa; Butt, Andrew
ABSTRACT: Planning practice and education require consideration of both universal and local norms and methods. It is often firmly embedded in localized issues and practices, yet students need to expand their career horizons and develop more critical, reflective understandings of planning issues in their 'home' environment. Internationalized curriculum provides a fertile environment for exploring cross-cultural encounter and reflexive practice using varied planning traditions to situate examples for teaching. The ethical and political implications of working internationally can, however, be masked within the seeming familiarity of shared planning language, concepts and techniques, and the apparent simplicity of comparative frames of reference. Planning is inherently political and contextual, yet the explicit dilemmas of the political and economic setting can, at first, appear hidden during a field project where the apparently universal notions of effective spatial planning are central to the dialogue amongst a diverse student group. Using the example of four joint field/project visits (2010–2014) involving Australian and Sri Lankan planning students in tsunami- and conflict-affected areas of Sri Lanka, this paper draws on student reflections and observations to explore the explicit encounters with ethical dilemmas, political settings, contingent problem-setting and the implications of these for planning practice within the home setting.